THE EFFECTIVENESS OF USING K-W-L TECHNIQUE TO INCREASE STUDENTS’ READING COMPREHENSION AT THE EIGHT GRADE OF SMP PGRI POOPO - Selvia Imelda Ratu; Jim R. Tuna; Sarah Kamagi (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2023)
This study aims to determine whether the K-W-L technique is effective in increasing students’ reading comprehension or not. This study was conducted at SMP PGRI Poopo. The subject in this study were class VIII for the academic year 2021/2022 which consisted of 20 students. The design of this study was pre-experimental with one group pre-test and post-test design. The pre-test was given before the treatment and post-test was given after the treatment. The data of this study is collection is through a given test. The data is analysis by comparing the mean score of the tests. Based on the results of the analysis, the mean score of the post-test (T2) is higher 83,75 than those of the pre-test (T1) 34,7. This means that students who were taught using the “KWL technique” scored higher in their reading comprehension that students who were not taught using the technique. So it can be concluded that the K-W-L technique is effective to increasing students’ reading comprehension.